(untitled) (Progressive Agriculture, 2013)
A cross was made between high yielding salt susceptible BINA variety (Binadhan-5) with salt tolerant rice landrace (Harkuch) to identify salt tolerant rice lines. Thirty six F3 rice lines of Binadhan-5 x Harkuch were tested for salinity tolerance at the seedling stage in hydroponic system using nutrient solution. In F3 population, six lines were found as salt tolerant and 10 lines were moderately tolerant based on phenotypic screening at the seedling stage. Twelve SSR markers were used for parental survey and among them three polymorphic SSR markers viz., OSR34, RM443 and RM169 were selected to evaluate 26 F3 rice lines for salt tolerance. With respect to marker OSR34, 15 lines were identified as salt tolerant, 9 lines were susceptible and 2 lines were heterozygous. While RM443 identified 3 tolerant, 14 susceptible and 9 heterozygous rice lines. Eight tolerant, 11 susceptible and 7 heterozygous lines were identified with the marker RM169. Thus the tested markers could be efficiently used for tagging salt tolerant genes in marker-assisted breeding programme. DOI: http://dx.doi.org/10.3329/pa.v19i2.16929 Progress. Agric. 19(2): 57 - 65, 2008